Asupan Karbohidrat dan Aktivitas Fisik dengan Kadar Glukosa Darah Puasa Penderita Diabetes Melitus Tipe 2 - taufiq atmadja; Salma Fadila Marwah; Nisatami Husnul (Nutrition Department, Poltekkes Kemenkes Tanjung Karang, 2025)
Diabetes mellitus is a metabolic disease that occurs because blood glucose levels increase due to impaired insulin secretion. The purpose of this study was to analyze the relationship between carbohydrate intake and physical activity with fasting blood glucose levels in patients with type 2 diabetes mellitus at Puskesmas Mangkubumi in 2025. We used a cross-sectional design with 72 subject selected by quota sampling method. Chi-square was used to data analyze. The results showed that the majority of respondents were female (68.1%), and aged 50-69 years (76.4%). The majority of respondents were in excess carbohydrate intake (41.7%), moderate physical activity (45.8%), and uncontrolled blood glucose levels (61.1%). Bivariate results showed carbohydrate intake (p=0.018) had a significant relationship with fasting blood glucose levels, while physical activity had no significant relationship with fasting blood glucose levels (p=0.128). Carbohydrate intake showed a significant association with fasting blood glucose levels, while physical activity is not significantly related to blood glucose levels in patients with T2DM.